Capital Structure and Firm’s Sustainability: Evidence from Malaysian Oil and Gas Companies at Bursa Malaysia - Hadi, Abdul Razak Bin Abdul (Ekonomi dan Bisnis, 2022)
This study looks into how capital structure theories explain capital structure characteristics of oil and gas companies in Malaysia